Rising Bilingual Children in Indonesian Context: Review of The Scientific Advantages - Afnesha Noveriana Chang; Suparmi Suparmi (Jurnal Ilmiah Langue and Parole, 2022)
Bilingual education has become very popular among Indonesian children nowadays. Other than learning it from school, they are also exposed to the second language in their homes. Although some misconceptions persist in society, some parents continue to do so because they believe that bilingualism benefits their children's development, whether in the language or cognitive areas. This paper focuses on the common misconceptions spreading among parents. This research was specifically done based on literature review. Here, the five common myths about bilingualism on early childhood were answered based on scientific explanations given by experts. The finding indicates that being bilingual helps children have strong language development and executive functioning at the same time. Results are interpreted in the context of relevant research and explained based on the theories of some experts.